The dynamic immune behavior of primary and metastatic ovarian carcinoma - Elaine Stur; Fuduan Peng; Pang-ning Teng; Emine Bayraktar; Min Hu; Sara Corvigno; David J. Brown; Sanghoon Lee; Kathleen N. Moore; Nicholas W. Bateman; Kathleen M. Darcy; George L. Maxwell; et al. (npj Precision Oncology)
Abstract Patients with high-grade serous ovarian carcinoma (HGSC) are usually diagnosed with advanced-stage disease, and the tumors often have immunosuppressive characteristics. Together, these factors are important for disease progression, drug resistance, and mortality. In this study, we used a combination of single-cell sequencing and spatial transcriptomics to identify the molecular mechanisms that lead to immunosuppression in HGSC. Primary tumors consistently showed a more active immune microenvironment than did omental tumors. In addition, we found that untreated primary tumors were mostly populated by dysfunctional CD4 and CD8 T cells in later stages of differentiation; this, in turn, was correlated with expression changes in the interferon α and γ pathways in epithelial cells, showing that cross-communication between the epithelial and immune compartments is important for immune suppression in HGSC. These findings could have implications for the design of clinical trials with immune-modulating drugs.